Covid-19 Pandemic and Financial System Stability in Indonesia - Irwandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine how the impact of the covid-19 pandemic on financial system stability in Indonesia. The quantitative data analysis method is used to look at the causes of a phenomenon by explaining the differences between two or more problem topics that are suspected to be interrelated. The results showed that the corona virus or Covid 19 resulted in the government having to issue several policies, namely through work from home (PSBB) which reduced economic activity, resulting in inequality in the economic sector which was far below the optimal business and financial turnover. On the other hand, economic growth in 2020 is predicted to weaken sharply from 5.02% (yoy) in 2019 to the range of -2% to -1% (yoy). Pressure also occurred on price stability in the first semester of 2020 due to the high uncertainty of global financial markets, both due to the spread of COVID-19 and the prospect of a weakening world economy. Likewise, inflationary pressures resulted in weak domestic demand. However, on the financial institution side, banks are still experiencing fairly good conditions during the pandemic. Financial institutions remain in the resilience of the financial system that is running. This can be seen from the capital actors, the amount of credit, and healthy liquidity